Sex difference in the association between creatinine-to-cystatin C ratio and metabolic syndrome among Chinese adults - Chen, Jo-Hsuan; Chen, Jau-Yuan; Chen, Yi-Chuan; Li, Wen-Cheng (Frontiers in Endocrinology, 2024)
Background: Metabolic syndrome (MetS), characterized by central obesity, insulin resistance, dyslipidemia, and hypertension, affects 20-25% of the global population. The creatinine-to-cystatin C ratio (CCR) is an indicator of skeletal muscle mass. While CCR may play a role in MetS development, sex differences in these associations are not fully understood. Therefore, this study aimed to investigate how CCR levels are associated with MetS in a Chinese adult population, focusing on possible sex disparities. Method: We conducted a retrospective cross-sectional analysis of 9,376 adults from Xiamen Chang Gung Hospital between 2014 to 2016. We examined the relationship between CCR and MetS, adjusting for cardiometabolic risk factors. Results: The prevalence of MetS was 24.7% in males and 18.0% in females. Interestingly, we observed significant sex differences in the association between CCR quartiles and MetS. Females in the lowest CCR quartile had a significantly higher risk of MetS (odds ratio=1.84). Receiver operating characteristic curve analysis revealed acceptable diagnostic power of CCR for MetS in females (area under the curve=0.65) but not in males. Conclusion: Our findings suggest that CCR is an independent risk factor for MetS in females, highlighting the importance of sex-specific assessments when evaluating MetS risk.